Characterization of the complete mitochondrial genome sequences of three Merulinidae corals and novel insights into the phylogenetics - Niu, Wentao (PeerJ, 2020)
Over the past few decades, modern coral taxonomy, combining morphology and molecular sequence data, has resolved many long-standing questions about scleractinian corals. In this study, we sequenced the complete mitochondrial genomes of three Merulinidae corals (Dipsastraea rotumana, Favites pentagona, and Hydnophora exesa) for the first time using next-generation sequencing. The obtained mitogenome sequences ranged from 16,466 bp (D. rotumana) to 18,006 bp (F. pentagona) in length, and included 13 unique protein-coding genes (PCGs), two transfer RNA genes, and two ribosomal RNA genes . Gene arrangement, nucleotide composition, and nucleotide bias of the three Merulinidae corals were canonically identical to each other and consistent with other scleractinian corals. We performed a Bayesian phylogenetic reconstruction based on 13 protein-coding sequences of 86 Scleractinia species. The results showed that the family Merulinidae was conventionally nested within the robust branch, with H. exesa clustered closely with F. pentagona and D. rotumana clustered closely with Favites abdita. This study provides novel insight into the phylogenetics of species within the family Merulinidae and the evolutionary relationships among different Scleractinia genera.